Risk Factors for Mortality in Abdominal Infection Patients in ICU: A Retrospective Study From 2011 to 2018 - Luo, Xingzheng; Li, Lulan; Ou, Shuhua; Zeng, Zhenhua; Chen, Zhongqing (Frontiers in Medicine, 2022)
To identify the risk factors related to the patient's 28-day mortality, we retrospectively reviewed the records of patients with intra-abdominal infections admitted to the ICU of Nanfang Hospital, Southern Medical University from 2011 to 2018. Multivariate Cox proportional hazard regression analysis was used to identify independent risk factors for mortality. 431 patients with intra-abdominal infections were analyzed in the study. The 28-day mortality stepwise increased with greater severity of disease expression: 3.5% in infected patients without sepsis, 7.6% in septic patients, and 30.9% in patients with septic shock (p < 0.001). In multivariate analysis, independent risk factors for 28-day mortality were underlying chronic diseases (adjusted HR 3.137, 95% CI 1.425-6.906), high Sequential Organ Failure Assessment (SOFA) score (adjusted HR 1.285, 95% CI 1.160-1.424), low hematocrit (adjusted HR 1.099, 95% CI 1.042-1.161), and receiving more fluid within 72 hours (adjusted HR 1.028, 95% CI 1.015-1.041). Compared to the first and last four years, the early use of antibiotics, the optimization of IAT strategies, and the restriction of positive fluid balance were related to the decline in mortality of IAIs in the later period. Therefore, underlying chronic diseases, high SOFA score, low hematocrit, and receiving more fluid within 72 hours after ICU admission were independent risk factors for patients’ poor prognosis.